Agency, Accommodation, and Acculturation in the Space of American Muslim Women - Madonna, Susan (Al-Adyan: Journal of Religious Studies, 2024)
This article aims to examine how immigrant Muslim women strive to create a space of recognition in American mosques. Based on selected books and articles that provide data on the agency, accommodation, and acculturation of American Muslim women in the context of the mosque as a religious center, this research reveals that immigrant Muslim women in America often show higher levels of participation in mosque services and activities compared to their counterparts in their countries of origin. Even in a progressive mosque in Cape Town, a woman was invited to deliver the Friday sermon, which is typically conducted by a male imam. While accommodation is clearly evident in the initiatives of agents, architects, and mosque designers in America who strive to meet the needs of women in future mosque constructions, mosques are also believed to play a crucial role in facilitating the acculturation process of immigrant Muslim women into the host society. In practice, immigrant community leaders and religious authorities interpret Islam in a futuristic and integrative manner, viewing the mosque as an evolving entity that grows and adapts to changing environments, thus effectively bridging its congregants with the broader society.Artikel ini bertujuan untuk melihat bagaimana perempuan Muslim imigran berupaya menciptakan ruang pengakuan di masjid-masjid Amerika. Berdasarkan buku-buku dan artikel-artikel terpilih yang memberikan data tentang agensi, akomodasi, dan akulturasi perempuan Muslim Amerika dalam konteks masjid sebagai pusat keagamaan, penelitian ini mengungkapkan bahwa perempuan Muslim imigran di Amerika seringkali menunjukkan tingkat partisipasi yang lebih tinggi dalam layanan dan kegiatan masjid dibandingkan dengan rekan-rekan mereka di negara asal. Bahkan di sebuah masjid progresif di Cape Town, seorang perempuan diundang untuk menyampaikan khotbah Jumat, yang biasanya dilakukan oleh imam laki-laki. Sementara akomodasi terlihat jelas dalam inisiatif para agen, arsitek, dan perancang masjid di Amerika yang berupaya mengakomodasi kebutuhan perempuan dalam pembangunan masjid di masa depan. Selain itu, masjid diyakini memainkan peran penting dalam memfasilitasi proses akulturasi perempuan Muslim imigran ke dalam masyarakat tuan rumah. Dalam praktiknya, para pemimpin komunitas imigran dan otoritas agama menafsirkan Islam secara futuristik dan integratif, memandang masjid sebagai entitas yang berevolusi, tumbuh, dan beradaptasi terhadap perubahan lingkungan, sehingga secara efektif menjembatani jamaahnya dengan masyarakat yang lebih luas.